The Identification Standard of “Serious Circumstances” in the Crime of Infringing Human Genetic Resources - Gong, Xuan (Transactions on Social Science, Education and Humanities Research, 2024)
As a condition for the crime of infringing human genetic resources, the “serious circumstances” are relatively vague in terms of concrete connotation and judgment criteria. In order to ensure the accuracy of judicial determination, it needs to be interpreted by legal hermeneutics. The “serious circumstances” in the crime of infringing human genetic resources should be located as “objective exceeding elements” in the criminal constitution system. The legal interests of the crime of infringing human genetic resources are “public health” and “security and administration order of public health”, and the bottom criterion of infringement of it is abstract danger. Based on this, “serious circumstances” should refer to the danger of illegal utilization of human genetic resources, and be specifically identified from both subjective and objective aspects.